Angiomyofibroblastoma of scalp: a rare soft tissue tumour at an unusual site - Hussain, Sajid (International Surgery Journal, 2020)
Angimyofibroblastoma is a very rare, benign mesenchymal soft tissue tumour which involves the vulvovaginal area of females of reproductive age group. These tumours are usually slow growing and painless which has a very low tendency for local recurrence. In women it is common in female genital tract, vulva, and posterior perivesical space. In men it occurs in spermatic cord. Here a report of 47 year old male patient from VMKV Medical College and Hospital, Salem was presented with a swelling in the posterior aspect of scalp from 6 months with no any associated symptoms. A preoperative diagnosis of dermoid scalp was made and patient was subjected for excision.